2015
DOI: 10.1017/s0950268814003446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of resistance to third-generation cephalosporins inShigellabetween Europe-America and Asia-Africa from 1998 to 2012

Abstract: We conducted a systematic review to compare resistance to third-generation cephalosporins (TGCs) in Shigella strains between Europe-America and Asia-Africa from 1998 to 2012 based on a literature search of computerized databases. In Asia-Africa, the prevalence of resistance of total and different subtypes to ceftriaxone, cefotaxime and ceftazidime increased markedly, with a total prevalence of resistance up to 14·2% [95% confidence interval (CI) 3·9-29·4], 22·6% (95% CI 4·8-48·6) and 6·2% (95% CI 3·8-9·1) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 45 publications
(54 reference statements)
0
22
0
1
Order By: Relevance
“…However, growing evidence supporting the link between shigellosis and chronic health consequences (e.g., reactive arthritis and irritable bowel syndrome) (35, 36), the association between travelers' diarrhea (TD) (treated and untreated) and colonization with extended-spectrum beta-lactamase-producing Enterobacteriaceae (37), as well as concern for multidrug-resistant strains of Shigella, further complicate treatment (6, 38, 39), making primary prevention a desired goal. More studies are needed to better understand the true prevalence of Shigella among travelers, with application of culture-independent diagnostic techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, growing evidence supporting the link between shigellosis and chronic health consequences (e.g., reactive arthritis and irritable bowel syndrome) (35, 36), the association between travelers' diarrhea (TD) (treated and untreated) and colonization with extended-spectrum beta-lactamase-producing Enterobacteriaceae (37), as well as concern for multidrug-resistant strains of Shigella, further complicate treatment (6, 38, 39), making primary prevention a desired goal. More studies are needed to better understand the true prevalence of Shigella among travelers, with application of culture-independent diagnostic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine development remains a high priority given the disease burden (4, 5), increasing antibiotic resistance (6), and an increasing appreciation of the postinfectious sequelae associated with shigellosis (7, 8). Shigella flexneri accounts for 30 to 60% of shigellosis cases in developing regions, necessitating coverage of prevalent S.…”
Section: Introductionmentioning
confidence: 99%
“…According to US National Antimicrobial Surveillance system data, 41 percent of Shigella species are resistant to ampicillin, 48 percent are resistant to TMP-SMX and 2 percent are resistant against ciprofloxacin, whereas ceftriaxone resistance was reported to be less than 1 percent in 2010 (10). There is an increasing resistance to aminoglycosides and quinolones in Asia and Africa, whereas resistance to ceftriaxone was reported to be less than 14.2 percent (11). In a study conducted in Turkey in 2002, resistance to TMP-SMX was reported to be 90.4 percent, whereas sensitivity to ampicillin was 86.4 percent, sensitivity to cefotaxime was 98 percent and sensitivity to ciprofloxacin was 100 percent (4).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quinolone resistance (PMQR) determinants are qnr, aac(6')-Ib-cr, and qepA [40,46]. Considering the above, monitoring of the drug resistance of Shigella strains should be strengthened, and rational use of antibiotics is required [17,50]. In addition, guidelines for therapy should be monitored and modified based on regional reports of resistance to antimicrobial agents [11].…”
Section: Discussionmentioning
confidence: 99%